Body of KnowledgeIklan Politik Televisi - Wijaya, Sri Herwindya Baskara (KOMUNITAS, 2014)
Begin campaign general electoral in 1999, world of political in Indonesia came in newÂ face.Â ManyÂ politicalÂ partyÂ beginÂ useÂ television mediaÂ toÂ makeÂ promotion. However in before general electoral, political party only use some media without televisionÂ suchÂ usÂ newspaper,Â radioÂ andÂ belowÂ theÂ lineÂ media.Â SoÂ far,Â some politicalÂ partyÂ haveÂ usedÂ televisionÂ toÂ advertising political.Â ThereÂ areÂ Partai Demokrat, Partai Golkar, PDIP, PKS, PAN, PKB, PPP, Partai Gerindra, Partai Hanura, etc up to new political party such is Partai Nasdem. Choosing television asÂ advertisingÂ mediaÂ becauseÂ reasonsÂ ofÂ massiveÂ and moreÂ âliveâÂ inÂ public perception.Â SoÂ itÂ needÂ exactlyÂ strategyÂ toÂ advertiseÂ inÂ televisionÂ especiallyÂ see some factor are track and record of political partyor candidate, time, message content, advertising creator, ethic and media distributor. Key words:Political party, political advertising, television